The Business Legal Policy in Indonesia, Ghana, and Vietnam: A Perspective from the Theory of Dignified Justice - I Gede Agus Kurniawan; Putu Aras Samsithawrati; Fradhana Putra Disantara; Mac Thi Hoai Thuong; Briggs Samuel Mawunyo Nutakor (Lex Scientia Law Review, 2025)
This study aims to compare business law policies in Indonesia, Ghana, and Vietnam from the perspective of dignified justice and analyze the challenges and opportunities in their implementation. This research employs a normative legal method with statutory, comparative, and conceptual approaches to analyze business law policies in Indonesia, Ghana, and Vietnam from the perspective of dignified justice. The study’s findings reveal that business law policies in Indonesia, Ghana, and Vietnam have unique characteristics influenced by their respective legal systems, histories, and socio-economic conditions. The main challenges include complex bureaucracy, regulatory uncertainty, weak law enforcement, and widespread corruption, which hinder transparency and fair business competition. Indonesia adopts a mixed legal system with reforms such as the Omnibus Law (Job Creation Law) to simplify regulations. However, it still faces issues in licensing and legal protection for SMEs. Ghana, operating under a common law system, seeks to strengthen corporate governance through the Companies Act 2019 but continues to struggle with capital access and burdensome bureaucracy for businesses. Meanwhile, Vietnam, with its socialist legal system, has encouraged private sector growth through reforms like the Law on Enterprises 2020 but still faces challenges related to regulatory transparency and labor protection. All three countries have opportunities to enhance economic competitiveness through bureaucratic digitalization, more transparent legal reforms, and broader support for SMEs and startups. With more inclusive and stable policies, they can establish a fairer and more sustainable business law system from the perspective of dignified justice.